English and Identity in Asia - Young, University of Wisconsin-Madison, USA, Richard F. (Asiatic: IIUM Journal of English Language and Literature, 2008)
A common assumption is that one’s mother tongue is essentially one’s ethnocultural identity.Contact by speakers of local languages with a hegemonic language such as English is therefore seen as endangering not only the local language but also threatening the identity that speakers deem closest to them. I will argue in this paper that identifying language with identity is an oversimplification. I present societal attitudes toward English in a number of East and Southeast Asian nations and discuss the roots of those attitudes. Macro-societal attitudes towards language are, however, only one factor in the construction of ethnocultural identity in face-to-face interaction. I borrow Bucholtz and Hall’s tactics of intersubjectivity to frame my case that personal identity is constructed and negotiated by language performance in oral and literate practices and it is neither determined nor fixed by the attitudes of a society toward languages.